KEANEKARAGAMAN SPESIES BURUNG DI HUTAN MANGROVE PULAU KELAGIAN BESAR PROVINSI LAMPUNG - Memo Dinda Nugraha; Agus Setiawan; Dian Iswandaru; Yulia Rahma Fitriana (Jurnal Belantara, 2021)
The existence of mangrove forests is very important in an area because as a habitat for various types of wildlife, especially birds. This study aims to determine the diversity of bird species in the Kelagian Besar Mangrove Forest, Lampung Province. Data on bird species diversity was obtained by the IPA (Indices Ponctual Abundance) method. Data collection of bird species by recording the type and number of individual birds found. Species identification also uses the method of bird recognition directly by people who know the birds in the area such as the local community or an expert on birds. Data obtained in the field are then analyzed using the Shanon-Winner diversity index formula. The results found 27 species of birds from 21 families with a total of 741 individual birds in the Kelagian Besar Mangrove Forest. While the diversity index value is 2.26 with medium index criteria. There are 8 protected bird species, namely the black-necked darautaut (Sterna sumatrana), the white-wing daralaut (Chlidonias leucopterus), the oyster daralaut (Gelochelidon nilotica), the white belly eagle (Haliaeetus leucogaste), the brontok eagle (Spizaetus cirrhatus), oyster belly Rhipidura javanica), sabine seagulls (Xema sabini), and large fissures (Fregata minor).